Fractal Theory in Thin Films: Literature Review and Bibliometric Evidence on Applications and Trends - Mwema, Fredrick M.; Jen, Tien-Chien; Kaspar, Pavel (Fractal and fractional, 2022)
A bibliometric analysis of publications on fractal theory and thin films is presented in this article. Bibliographic information is extracted from the Web of Science digital database and the bibliographic mapping undertaken using VOSviewer software. Based on the analysis, there is a growing trend in research on the applications of fractal theory in thin film technology. The factors driving this trend are discussed in the article. The co-citation, co-authorship and bibliographic coupling among authors, institutions and regions are presented. The applications of fractal theory in thin film technology are clarified based on the bibliometric study and the directions for future research provided.